Modulation of BK channels contributes to activity-dependent increase of excitability through MTORC1 activity in CA1 pyramidal cells of mouse hippocampus - Springer, Steven J.; Burkett, Brian J.; Schrader, Laura A. (Frontiers in Cellular Neuroscience, 2015)
Memory acquisition and synaptic plasticity are accompanied by changes in the intrinsic excitability of CA1 pyramidal neurons. These activity-dependent changes in excitability are mediated by modulation of intrinsic currents which alters the responsiveness of the cell to synaptic inputs. The afterhyperpolarization, a major contributor to the regulation of neuronal excitability, is reduced in animals that have acquired several types of hippocampus-dependent memory tasks and also following synaptic potentiation by high frequency stimulation. BK channels underlie the fast afterhyperpolarization and contribute to spike repolarization, and this afterhyperpolarization is reduced in animals that successfully acquired trace-eyeblink conditioning. This suggests that BK channel function is activity-dependent, but the mechanisms are unknown. In this study, we found that blockade of BK channels with paxilline (10µM) increased spike half-width and instantaneous frequency in response to a +100pA depolarization. In addition, induction of LTP by theta burst stimulation (TBS) in CA1 pyramidal neurons reduced BK channel’s contribution to spike repolarization and instantaneous frequency. This result indicates that BK channel activity is decreased following synaptic potentiation. Interestingly, blockade of mammalian target of rapamycin (MTORC1) with rapamycin (400 nM) following synaptic potentiation restored BK channel function, suggesting a role for protein translation in signaling events which decreased postsynaptic BK channel activity following synaptic potentiation.